1985
DOI: 10.1073/pnas.82.13.4365
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of ornithine decarboxylase activity by insulin and growth factors is mediated by amino acids.

Abstract: The polypeptide growth factors, nerve growth factor, epidermal growth factor, and platelet-derived growth factor, as well as insulin do not induce ornithine decarboxylase (L-ornithine carboxy-lyase, EC 4.1.1.17) unless a minimal concentration of an ornithine decarboxylase-inducing amino acid, such as asparagine, is present in the medium. The effects of the growth factors were studied in appropriately responsive cell lines: pheochromocytoma (PC12) cells for nerve and epidermal growth factors, fibroblasts (NIH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In contrast, studies with several cell lines [40,41] have demonstrated that loading cells with System A amino acids, including the nonmetabolisable alpha‐amino‐isobutyrate [41], mimics the action of insulin and other growth factors [40,41]. Such potentially anabolic effects only occur at very high intracellular amino acid concentrations [40,41] but such concentrations are attained in a few hours in L6‐G8C5 cells exposed to high extracellular concentrations of MeAIB (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies with several cell lines [40,41] have demonstrated that loading cells with System A amino acids, including the nonmetabolisable alpha‐amino‐isobutyrate [41], mimics the action of insulin and other growth factors [40,41]. Such potentially anabolic effects only occur at very high intracellular amino acid concentrations [40,41] but such concentrations are attained in a few hours in L6‐G8C5 cells exposed to high extracellular concentrations of MeAIB (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…Basal levels of ODC are low, but enzyme activity increases rapidly in response to a variety of stimuli, including growth factors, insulin, stress, and certain amino acids (Wang and Johnson 1991, Rinehart and Canellakis 1985). ODC has one of the shortest half-lives of any mammalian enzyme and is feedback regulated by polyamines which induce the synthesis of an inhibitor called antizyme (Heller et al, 1976).…”
Section: Polyaminesmentioning
confidence: 99%
“…Although ASN was the most effective, other amino acids transported by one of the Na + -dependent systems could also induce ODC activity (Rinehart et al 1985). Of particular interest was the finding that, in a variety of cell types, the induction of ODC by growth factors and hormones required the presence of ASN, GLN or a similar amino acid (Rinehart and Canellakis, 1985). Neither epidermal growth factor (EGF), nerve growth factor, nor insulin could induce ODC activity unless ASN was present in the medium.…”
Section: Polyaminesmentioning
confidence: 99%
“…In the present study, an attempt was made to assess the degree of hormonal stimulation of individual small, non-atretic ovarian follicles by measuring their ornithine decarboxylase activity (L-ornithine carboxy-lyase; EC 4.1.1.17) in relation to follicular size and location within the ovary. This enzyme catalyses the ratelimiting reaction in the biosynthesis of the polyamines, spermidine and spennine (Pegg & Williams-Ashman, 1968) and its activity increases substantially in response to a variety of trophic stimuli including hormones, tumour promoters, nutrient availability and organ regeneration (Schorock, Oakman & Butcher, 1970;Veldhuis & Sweinberg, 1981;Jetten, Ganong, Vandenbark et al 1985;Rinehart & Canellakis, 1985). Its activity is closely related to tissue growth.…”
Section: Introductionmentioning
confidence: 97%